Nutritional and aroma improvement of gluten-free bread: is bee pollen effective?. (January 2020) - Conte, P.; Del Caro, A.; Urgeghe, P.P.; Petretto, G.L.; Montanari, L.; Piga, A.; Fadda, C.
Abstract: The impact of the addition of bee pollen (BP) (1, 2, 3, 4, and 5%) on the nutritional, bioactive and aroma composition of technologically viable gluten-free (GF) breads has been studied. The content of some macroconstituents (such as protein and lipids), minerals (K, Ca, Mg, Fe, Cu, Mn), and phytochemicals (carotenoids), the composition of biologically active compounds (soluble, insoluble and bioaccessible polyphenols), the antioxidant activity and the aroma profile of breads were investigated. The incorporation of BP into GF breads increased proteins, minerals, soluble and bioaccessible polyphenols, total carotenoids, and antiradical activity at almost all levels (2%–5%). Improvements in the phenolics composition of the resulting breads, as evidenced by a decrease in the insoluble/soluble polyphenols ratio (from 8.7 in the control to 4.2 in the breads with 4% and 5% of BP) and a concomitant increase in the polyphenol bioacessibility (36% rise in the bread with 5% of BP) in comparison to the control were also observed. BP did not affect the lipids content and the mineral composition, except for K and Ca. 48 volatile compounds were found in the examined breads, but only 5, namely pyrazinamide, 5-methyl-2-furaldehyde, 2-acetylfuran, furfural, 2-pentyl-furan, seemed to increase according to BP supplementation. Highlights: Nutritional and bioactive properties of gluten-free breads were improved by bee pollen supplementation. Fortified gluten-free breads exhibited better distribution of polyphenol fractions and higher antioxidant activity. The addition of bee pollen improved the aromatic profile of gluten-free breads.